Comprehensive evaluation of time-varied outcomes for invasive and conservative strategies in patients with NSTE-ACS: a meta-analysis of randomized controlled trials - Zhao, Yi-Jing; Sun, Yangyang; Wang, Fan; Cai, Yuan-Yuan; Alolga, Raphael N.; Qi, Lian-Wen; Xiao, Pingxi (Frontiers in Cardiovascular Medicine, 2023)
Background Results from randomized controlled trials (RCTs) and meta-analyses comparing invasive and conservative strategies in patients with non-ST-elevation acute coronary syndrome (NSTE-ACS) are highly debatable. We systematically evaluate the efficacy of invasive and conservative strategies in NSTE-ACS based on time-varied outcomes. Methods The RCTs for the invasive versus conservative strategies were identified by searching PubMed, Cochrane Central Register of Controlled Trials, Embase, and ClinicalTrials.gov. Trial data for studies with a minimum follow-up time of 30 days were included. We categorized the follow-up time into six varied periods, namely, ≤6 months, 1 year, 2 years, 3 years, 5 years, and ≥10 years. The time-varied outcomes were major adverse cardiovascular event (MACE), death, myocardial infarction (MI), rehospitalization, cardiovascular death, bleeding, in-hospital death, and in-hospital bleeding. Risk ratios (RRs) and 95% confidence intervals (Cis) were calculated. The random effects model was used. Results This meta-analysis included 30 articles of 17 RCTs involving 12,331 participants. We found that the invasive strategy did not provide appreciable benefits for NSTE-ACS in terms of MACE, death, and cardiovascular death at all time points compared with the conservative strategy. Although the risk of MI was reduced within 6 months (RR 0.80, 95% CI 0.68–0.94) for the invasive strategy, no significant differences were observed in other periods. The invasive strategy reduced the rehospitalization rate within 6 months (RR 0.69, 95% CI 0.52–0.90), 1 year (RR 0.73, 95% CI 0.63–0.86), and 2 years (RR 0.77, 95% CI 0.60–1.00). Of note, an increased risk of bleeding (RR 1.80, 95% CI 1.28–2.54) and in-hospital bleeding (RR 2.17, 95% CI 1.52–3.10) was observed for the invasive strategy within 6 months. In subgroups stratified by high-risk features, the invasive strategy decreased MACE for patients aged ≥65 years within 6 months (RR 0.68, 95% CI 0.58–0.78) and 1 year (RR 0.75, 95% CI 0.62–0.91) and showed benefits for men within 6 months (RR 0.71, 95% CI 0.55–0.92). In other subgroups stratified according to diabetes, ST-segment deviation, and troponin levels, no significant differences were observed between the two strategies. Conclusions An invasive strategy is superior to a conservative strategy in reducing early events for MI and rehospitalizations, but the invasive strategy did not improve the prognosis in long-term outcomes for patients with NSTE-ACS. Systematic Review Registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42021289579, identifier PROSPERO 2021 CRD42021289579.